2021
DOI: 10.3389/fcell.2021.731712
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Porcine lncMGPF Regulate Meat Production Traits by Affecting RNA Stability

Abstract: lncMGPF is a novel positive regulator of myogenic differentiation, muscle growth and regeneration in mouse, pig, and human. But whether natural mutations within lncMGPF gene regulate animal meat production traits is unclear. In this study, ten single nucleotide polymorphisms (SNPs) of pig lncMGPF (plncMGPF) gene were identified among commercial pig breeds and Chinese local pig breeds. These SNPs are highly linked and constructed into multiple haplotypes, and haplotype ATTCATGTTC (H1) mainly exists in commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Chen et al [ 39 ] pointed out that circMYBPC1 can directly bind MyHC protein, promote the differentiation of myoblasts, and possibly promote skeletal muscle regeneration. One study showed that LncMGPF promoted the expression of HuR in C2C12 cytoplasm, enhancing the stability of MyoD and MyoG mRNA, and thus promoting myogenesis [ 40 , 41 ]. In this study, we found that PURB and the TTN promoter have a binding motif through the use of the UCSC genome browser and PROMO database, and we found that circTTN overexpression promoted the binding of PURB and the TTN promoter and inhibited the generation of the TTN gene.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 39 ] pointed out that circMYBPC1 can directly bind MyHC protein, promote the differentiation of myoblasts, and possibly promote skeletal muscle regeneration. One study showed that LncMGPF promoted the expression of HuR in C2C12 cytoplasm, enhancing the stability of MyoD and MyoG mRNA, and thus promoting myogenesis [ 40 , 41 ]. In this study, we found that PURB and the TTN promoter have a binding motif through the use of the UCSC genome browser and PROMO database, and we found that circTTN overexpression promoted the binding of PURB and the TTN promoter and inhibited the generation of the TTN gene.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lncMGPF promoted human antigen R (HuR)-mediated mRNA stabilization of both MyoD and myogenin ( Figure 1 , left panel) [ 83 ]. Interestingly, 10 single nucleotide polymorphisms (SNPs) in pig lncMGPF have been identified in commercial and Chinese local pig breeds [ 84 ]. These SNPs are linked to lncMGPF stability and skeletal muscle growth.…”
Section: Myogenic Differentiation-related Lncrnasmentioning
confidence: 99%
“…In addition, SNPs located in lncRNAs can affect the expression level of ln-cRNAs by modifying their secondary structures. For example, SNPs in the lncMGPF gene can affect the secondary structures and stability of RNA, thereby regulating the growth and development of muscle (Lv et al, 2021). However, only very few functional SNPs in lncRNAs have been identified until now.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, relevant databases containing porcine lncRNAs, such as ALDB (Li et al., 2015), LncRNAnet (Liang et al., 2018), NONCODEV5 (Fang et al., 2018) and lncRNASNP v3 (Yang et al., 2022), have been established successively. Moreover, many functional lncRNAs affecting muscle growth and development have been identified, such as H19 (Li et al., 2020), Neat1 (Wang et al., 2020), MEG3 (Cheng et al., 2020) and plncMGPF (Lv et al., 2021).…”
Section: Introductionmentioning
confidence: 99%